Delano’s Turn: Directions West of the River - Andresen, Spencer; Borelli, Taryn; Borwege, Cody; Dalke, Madison; Estabrook, Samatha; Huerta, Esteban; Johnson, Jacob; McCaffrey, Patrick; Mccoy, Matt; Nichols, Avery; Schulte, Janna; Shrestha, Priyasha; et al. (Kansas State University. College of Architecture, Planning & Design, Department of Landscape Architecture and Regional & Community Planning, 2017)
Delano has been waiting. Although plans for community investment have been considered since 1989, there remains much to be done. Douglas Avenue has been redeveloped and is widely considered a tremendous success, yet the vacant Pacific Union rail corridor lays dormant, the Arkansas Riverfront is underdeveloped, vacant parcels and underutilized surface parking areas abound, and access to public space is fragmented. Recently, there are reasons for enthusiasm. Near the turn in the Arkansas River, a new residential building and an advanced learning library are under construction. Immediately adjacent, a hotel and mixed use residential building are slated for development. Wichita leadership wants to expand urban investment from the east side of the river to the west, including a renovated or redeveloped Lawrence-Dumont baseball stadium. There are many directions the community can turn. Showcasing Delano’s unique identity, leveraging existing assets, and creating cohesion are ways to move forward. Delano has been waiting. It’s Delano’s turn. Delano’s Turn: Directions West of the River presents urban design ideas for the future of the Delano district in Wichita, Kansas. Fifteen mid-level students enrolled in an intensive 8-week Community Planning and Design studio completed the work during the summer of 2017. The studio was co-led by Associate Professor Blake Belanger and Associate Professor Howard Hahn. The effort was supported with funding from the Wichita Downtown Development Corporation (WDDC) and Kansas State University’s Technical Assistance to Brownfields (TAB), and would not have been possible without the support of Blase Leven, TAB Program Coordinator. We are also grateful for the support and guidance from Jason Gregory with the WDDC, Scott Knebel with the Wichita-Sedgwick County Planning Department (WSCPD), and our external reviewers, particularly Associate Professor Carl Smith who delivered both exceptional insights and humor. Conceived by the studio professors and the WDDC, the idea for the project emerged from discussions in late 2016. Goals of the collaborative service learning studio included providing students with first-hand experience working with a community, generating creative ideas for advancing the dialogue about planning the future of Delano, engaging residents and stakeholders and responding to their input, and supporting the mission of the project partners. The studio’s process included rigorous mapping of various conditions, two community engagement workshops, design development through an iterative process, a final presentation to project partners and local planning and design professionals, and a public open house exhibiting posters of student proposals. Delano’s Turn is presented in two Volumes. Volume 1: Design Proposals begins with background, primary dilemmas, intent, methods, and process. In the following four chapters of Volume 1, we present specific urban design strategies for activating existing assets, showcasing Delano’s identity through sense of place, and increasing connectivity and cohesiveness. Volume 2: Critical Maps and Index contains over 80 maps documenting existing conditions, dilemmas, opportunities, and conceptual strategies. The maps served the studio as a vital method for developing urban design strategies. For planners and designers advancing this work, the critical maps are valuable research that may help inform recommendations and decision-making processes. In contrast to a singular master plan, the collection of ideas presented in Delano’s Turn provides a multitude of ideas that can be compared, evaluated, prioritized, and perhaps hybridized. We aspire that Delano’s Turn will contribute to the ongoing dialogue about the future direction of Delano, and will help establish a legacy for Wichita.
Keywords: Community Planning and Design; Landscape Architecture; Pacific Union rail corridor; Urban Design; Wichita Downtown Development Corporation (WDDC); Kansas State University’s Technical Assistance to Brownfields (TAB)